If f ( x ) = ( 1 − x ) n , then find the value of the expression below:
f ( 0 ) + f ′ ( 0 ) + 2 ! f ′ ′ ( 0 ) + 3 ! f ′ ′ ′ ( 0 ) + ⋯ + n ! f ( n ) ( 0 )
Notation: f ( k ) denotes the k th derivative of f ( x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It should be ∑ k = 0 n ( − 1 ) k ( k n ) ( 1 − x ) n − k = ∑ k = 0 n ( − 1 ) n − k ( k n ) ( 1 − x ) k = ( − 1 + 1 − x ) n = ( − x ) n . Hence, g ( x ) = ( − x ) n . This does not affect the answer though.
We can see that the expression that we want is 1-nC0+nC1-nC2+...(-1)^(n-1) x nCn which is the binomial expansion of (1-x)^n when x is 1. So since the expression and f(x) are equal at x=1, by putting x=1 in f(x) gives the answer as 0
Problem Loading...
Note Loading...
Set Loading...
g ( x ) = f ( x ) + f ′ ( x ) + 2 ! f ′ ′ ( x ) + 3 ! f ′ ′ ′ ( x ) + ⋯ + n ! f ( n ) ( x ) = 0 ! ( 1 − x ) n + 1 ! − n ( 1 − x ) n − 1 + 2 ! n ( n − 1 ) ( 1 − x ) n − 2 + 3 ! − n ( n − 1 ) ( n − 2 ) ( 1 − x ) n − 3 + ⋯ + n ! ( − 1 ) n n ( n − 1 ) ⋯ 3 ⋅ 2 ⋅ 1 ( 1 − x ) 0 = k = 0 ∑ n k ! ( n − k ) ! ( − 1 ) k n ! ( 1 − x ) n − k = k = 0 ∑ n ( − 1 ) n ( k n ) ( 1 − x ) n − k = k = 0 ∑ n ( − 1 ) n ( k n ) ( 1 − x ) k = ( 1 − ( 1 − x ) ) n = x n
⟹ g ( 0 ) = 0 n = 0